The angiotensin-converting enzyme 2 (ACE2) receptor in the prevention and treatment of COVID-19 are distinctly different paradigms - Craig Steven McLachlan (BMC, 2020)
Abstract There is current debate concerning the use of angiotensin-converting enzyme (ACE) inhibitors or angiotensin II type 1 receptor blockers (ARBs), for hypertension management, during COVID-19 infection. Specifically, the suggestion has been made that ACE inhibitors or ARBs could theoretically contribute to infection via increasing ACE2 receptor expression and hence increase viral load. The ACE2 receptor is responsible for binding the SAR-CoV2 viral spike and causing COVID-19 infection. What makes the argument somewhat obtuse for ACE inhibitors or ARBs is that ACE2 receptor expression can be increased by compounds that activate or increase the expression of SIRT1. Henceforth common dietary interventions, vitamins and nutrients may directly or indirectly influence the cellular expression of the ACE2 receptor. There are many common compounds that can increase the expression of the ACE2 receptor including Vitamin C, Metformin, Resveratrol, Vitamin B3 and Vitamin D. It is important to acknowledge that down-regulation or blocking the cellular ACE2 receptor will likely be pro-inflammatory and may contribute to end organ pathology and mortality in COVID-19. In conclusion from the perspective of the ACE2 receptor, COVID-19 prevention and treatment are distinctly different. This letter reflects on this current debate and suggests angiotensin-converting enzyme inhibitors and ARBs are likely beneficial during COVID-19 infection for hypertensive and normotensive patients.